Lisístrata: estudo e adaptatradução para o teatro de bonecos - Araujo, Danielle Motta (2017)
The main objectives of the dissertation are: the dissemination of Aristophanes Greek comedy through an adaptation / translation of the play Lysistrata (411 BC) for the genre Puppets Theater, with the intention of making accessible to another audience, not only to the erudite; the valorization of the regional speeches, especially those of Fortaleza, with the use of innumerable marks of oral communication in the script; and the promotion of the Paideia Group. In chapter two, it treats some concepts of translation and adaptation, so that a hybrid concept between the two types, which is used by the author and which is called adaptatranslation. Comments about other translations and adaptations of the play in question. The third chapter is devoted to the comparative study between the mask and the puppets, involving the scenic function and reaction of the audience, and comments the history of the Puppet Theater in the world. It also presents the process of confection of the puppets, setting and play-acting of other plays of the Paideia Group. Another chapter brings an annotated summary of the comedy Lysistrata, the historical context in which the play is inserted and the importance of the revival of this play by the Paideia Group currently. In the end, describes the process of adaptatranslation of the play for the Puppet genre in the regional parlance, and then exposing the adaptatranslated text. The results of this experiment will exposed in the conclusion, which will confirm the popularization of the classic play, even being play-acting in the genre Puppets Theater and in another cultural context.